Bio-delignification and Pre-treatment of Oil Palm Frond (OPF) by "Trametes Polyzona" for Enhanced Biochemical Methane Potential (BMP) - Mahmud, Muhammad Nazmi; Mohd, Masratul Hawa; Awang, Nik Azimatolakma; Zaidi, Nur Syamimi (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study aims to optimize pre-treatment conditions for oil palm fronds (OPF) using white rot fungi (WRF) species, "Trametes Polyzona" for enhancement of biogas production via biochemical methane potential (BMP) test. BMP tests were run under three conditions: OPF alone (control), OPF treated with "Trametes Polyzona", and OPF treated with "Trametes Polyzona" and supplement of water. Visual structures, FTIR, Klason method and GCMS were used to investigate the effect of pre-treatments conditions on bio-delignification process of OPF.
Keywords: Bio-Delignification; biochemical methane potential (BMP); oil palm fronds (OPF); white rot fungi (WRF)